Nanotube‐like processes facilitate material transfer between photoreceptors. (8th September 2021) - Kalargyrou, Aikaterini A; Basche, Mark; Hare, Aura; West, Emma L; Smith, Alexander J; Ali, Robin R; Pearson, Rachael A
Abstract: Neuronal communication is typically mediated via synapses and gap junctions. New forms of intercellular communication, including nanotubes (NTs) and extracellular vesicles (EVs), have been described for non‐neuronal cells, but their role in neuronal communication is not known. Recently, transfer of cytoplasmic material between donor and host neurons ("material transfer") was shown to occur after photoreceptor transplantation. The cellular mechanism(s) underlying this surprising finding are unknown. Here, using transplantation, primary neuronal cultures and the generation of chimeric retinae, we show for the first time that mammalian photoreceptor neurons can form open‐end NT‐like processes. These processes permit the transfer of cytoplasmic and membrane‐bound molecules in culture and after transplantation and can mediate gain‐of‐function in the acceptor cells. Rarely, organelles were also observed to transfer. Strikingly, use of chimeric retinae revealed that material transfer can occur between photoreceptors in the intact adult retina. Conversely, while photoreceptors are capable of releasing EVs, at least in culture, these are taken up by glia and not by retinal neurons. Our findings provide the first evidence of functional NT‐like processes forming between sensory neurons in culture and in vivo . Synopsis: Photoreceptors form type I and type II nanotubes ( Ph NTs) that mediate the transfer of cytoplasmic proteins and lipid‐bound molecules and, rarely, organelles, to other photoreceptors. Ph NTs mediate material transfer during photoreceptor transplantation in an actin dependent manner. Chimeric retinae reveal material transfer occurring between photoreceptors in vivo . Photoreceptors can release EVs containing photoreceptor‐specific cargo in culture, which show preferential uptake by Muller Glia in culture and  in vivo, but these do not mediate material transfer. Mammalian photoreceptor neurons form open‐end nanotubes that mediate the exchange of cytoplasmic and membrane‐bound molecules, or material transfer, which can result in gain of function in the acceptor cells. Abstract : Mammalian photoreceptor neurons form open‐end nanotubes that mediate the exchange of cytoplasmic and membrane‐bound molecules, or material transfer, which can result in gain of function in the acceptor cells.